Which sexually active young female students are most at risk of pelvic inflammatory disease? A prospective study. (16th June 2015) - Hay, Phillip E; Kerry, Sarah R; Normansell, Rebecca; Horner, Paddy J; Reid, Fiona; Kerry, Sally M; Prime, Katia; Williams, Elizabeth; Simms, Ian; Aghaizu, Adamma; Jensen, Jorgen; Oakeshott, Pippa
Abstract : Objective: To identify risk factors for pelvic inflammatory disease (PID) in female students. Methods: We performed a prospective study set in 11 universities and 9 further education colleges in London. In 2004–2006, 2529 sexually experienced, multiethnic, female students, mean age 20.8 years, provided self-taken vaginal samples and completed questionnaires at recruitment to the Prevention of Pelvic Infection chlamydia screening trial. After 12 months, they were followed up by questionnaire backed by medical record search and assessed for PID by blinded genitourinary medicine physicians. Results: Of 2004 (79%) participants who reported numbers of sexual partners during follow-up, 32 (1.6%, 95% CI 1.1% to 2.2%) were diagnosed with PID. The strongest predictor of PID was baseline Chlamydia trachomatis (relative risk (RR) 5.7, 95% CI 2.6 to 15.6). After adjustment for baseline C. trachomatis, significant predictors of PID were ≥2 sexual partners or a new sexual partner during follow-up (RR 4.0, 95% CI 1.8 to 8.5; RR 2.8, 95% CI 1.3 to 6.3), age <20 years (RR 3.3, 95% CI 1.5 to 7.0), recruitment from a further education college rather than a university (RR 2.6, 95% CI 1.3 to 5.3) and history at baseline of vaginal discharge (RR 2.7, 95% CI 1.2 to 5.8) or pelvic pain (RR 4.1, 95% CI 2.0 to 8.3) in the previous six months. Bacterial vaginosis and Mycoplasma genitalium infection were no longer significantly associated with PID after adjustment for baseline C. trachomatis . Conclusions: Multiple or new partners in the last 12 months, age <20 years and attending a further education college rather than a university were risk factors for PID after adjustment for baseline C. trachomatis infection. Sexual health education and screening programmes could be targeted at these high-risk groups. Trial registration number: (ClinicalTrials.gov NCT00115388 ).